Preventing Conflict in Resource-Rich Countries : The Extractive Industries Value Chain as a Framework for Conflict Prevention - Ríos, Mauricio O. (World Bank, Washington, DC, 2016)
For many developing countries, natural resource exports such as oil, diamonds and copper continue to be important drivers for economic growth and provide a unique opportunity for generating revenues for much-needed infrastructure and human development. Dependence on extractive resources, however, may also increase the likelihood of underdevelopment, fragility and conflict. The challenges for managing these resources efficiently are likely to expand, as a growing number of developing countries and fragile states emerge as oil and mineral producers. Thus, there is a need to gain a better understanding of the factors that may help prevent violent conflict in resource rich countries. This paper proposes that one way of gaining such understanding and insight is to “conflict-sensitize” the Extractive Industries Value Chain (EIVC), and use it as a framework for conflict prevention in resource-rich countries. In this context, the report’s main objective is to examine the potential opportunities for conflict prevention along the extractive industries value chain. Such a body of knowledge can help the World Bank, the UN and EU, as well as client countries and other partners, in their planning and coordination of complementary activities when implementing their programmes and projects, particularly when working in the same resource-rich countries. This paper aims to demonstrate the feasibility and challenges faced by adopting a conflict-sensitive approach within the World Bank’s EI Value Chain. The methodology used was a combined desk review and in-depth interviews with regional and country specialists, especially in governance/conflict prevention and extractive industries (Annex 1). The emphasis is on qualitative analysis. The four countries that were desk reviewed for the project, including Chile, Peru, the Democratic Republic of Congo (DRC), and Zambia, are all copper producers and were selected due to their heavy dependence on revenues from mining. This book is arranged as follows: (i) part one explains extractives, conflict prevention and the value chain; (ii) part two is about the EI value chain as framework for conflict prevention; (iii) part three talks about emerging themes and recommendation; and (iv) part four describes the four country examples and the emerging lessons.